“Narrar mi Ciudad” on Networks.: Communicative strategy for online socialization of a participatory audiovisual literacy project - Herrera Barreda, Dagmar; López Montoto, Laura (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The article presents the communicative online socialization strategy of Narrar mi Ciudad, an audiovisual literacy project for the rediscovery of heritage resulting from the participatory diagnosis of the skills and presence in networks of its members, the contrast with theory and similar experiences. Participatory Action Research is used as a methodology and bibliographic-documentary research, survey, content analysis, group participatory techniques typical of the selected methodology and triangulation are used as techniques. The resulting strategy offers the possibility of socializing the project and meets the training objective of generating skills for the conscious use of social networks in new generations.